2016
DOI: 10.1111/imm.12621
|View full text |Cite
|
Sign up to set email alerts
|

Reduced immunogenicity of Plasmodium falciparum gamete surface antigen (Pfs48/45) in mice after disruption of disulphide bonds – evaluating effect of interferon‐γ‐inducible lysosomal thiol reductase

Abstract: SummarySexual stages of Plasmodium are critical for malaria transmission and stage-specific antigens are important targets for development of malaria transmission-blocking vaccines. Plasmodium falciparum gamete surface antigen (Pfs48/45) is important for male gamete fertility and is being pursued as a candidate vaccine antigen. Vaccine-induced transmission-blocking antibodies recognize reduction-sensitive conformational epitopes in Pfs48/45. Processing and presentation of such disulphide-bondconstrained epitop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Fragment F1, F4 and F5 were also recognized differentially by some of the sera tested. A similar pattern of recognition has been observed in previous observation in which anti-Pfs48/45 immune sera were tested against the same panel of Pfs48/45 fragments [ 29 ]. Previous studies have shown that the two cysteine-rich subdomains of Pfs48/45 at the amino- and carboxyl- termini can induce transmission blocking antibody responses in experimental animals [ 12 , 27 ].…”
Section: Discussionsupporting
confidence: 82%
“…Fragment F1, F4 and F5 were also recognized differentially by some of the sera tested. A similar pattern of recognition has been observed in previous observation in which anti-Pfs48/45 immune sera were tested against the same panel of Pfs48/45 fragments [ 29 ]. Previous studies have shown that the two cysteine-rich subdomains of Pfs48/45 at the amino- and carboxyl- termini can induce transmission blocking antibody responses in experimental animals [ 12 , 27 ].…”
Section: Discussionsupporting
confidence: 82%
“…Various technical limitations have restricted progress towards the development of TBV vaccine based on Pfs48/45. It has been difficult to express Pfs48/45 in appropriate conformation in recombinant expression systems and reduced and alkylated form of Pfs48/45 has been shown to be poorly immunogenic [45]. While epitope analysis of Pfs48/45 has revealed surface targets of transmission blocking monoclonal antibodies [46], lack of any structural information and knowledge of conformational target epitopes has resulted in limited success in the development of recombinant TBV based on Pfs48/45.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Pfs230, Pfs48/45 is a transmission-blocking vaccine candidate and correct epitope conformation is also very important for eliciting effective blocking antibodies, however, protection is not complement-dependent (Vermeulen et al, 1985b; Carter et al, 1990; Targett, 1990; Roeffen et al, 1996; Healer et al, 1997; Milek et al, 1998b; Merino et al, 2016). The best epitope for blocking transmission was originally mapped to the third s48/45 domain at the C-terminus, however more recent constructs include different regions or even the full-length protein (Carter et al, 1990; Outchkourov et al, 2007, 2008; Chowdhury et al, 2009; Kapulu et al, 2015; Singh et al, 2015).…”
Section: 6-cys Proteins In the Sexual Stagesmentioning
confidence: 99%